Breaking and Instability Movement Characteristics of High-Position Double-Layer Hard Thick Strata due to Longwall Mining - Pu Wang; Jinquan Jiang; Bin Xu (Shock and Vibration)
With multilayer hard roof occurring above the mining area, the strata behaviors will be significantly affected by their special characteristics and interaction. In this paper, relying on the mining background of panel 1061 of a coalmine, the breaking instability of double-layer hard thick strata (DLHTS) and the precursory information of disasters are studied by using theoretical analysis, numerical simulation, and physical simulation. Results show that the DLHTS have bearing, blocking, and controlling effects. Prior to DLHTS breaking, the horizontal development of stress concentration zone and plastic zone can be controlled, and the overburden movement is gentle, while during the breaking process, the stress drops abruptly, the plastic zone expands longitudinally rapidly, the overburden moves notably, and the energy release is sharp, which is likely to directly cause strong dynamic pressure. Moreover, the DLHTS can interact with and influence each other; that is to say, the breaking of lower magmatic rock (LMR) can provide sufficient space for that of upper magmatic rock (UMR), while the UMR breaking can promote the LMR periodic breaking in turn and cause its secondary instability, thereby easily causing complex or composite dynamic disasters’ formation. Hence, compared with single hard thick stratum occurrence, the strata behaviors affected by DLHTS breaking and instability are normal and more intense. Study results can provide a scientific basis for the prevention and control of dynamic disaster with hard thick stratum occurrence and important guidance value for promoting safe and efficient production of coalmines.